The Cost of a Voluntary Task Switch - Arrington, Catherine M.; Logan, Gordon D. (Psychological Science, 2004)
Task-switching paradigms are widely used to study executive control. However, standard paradigms may not require active control to switch tasks. We examined voluntary task switching by having subjects choose which task to perform on a series of bivalent stimuli. Subjects performed parity or magnitude judgments on single digits. Instructions were to perform the two tasks equally often and in a random order. The response-to-stimulus interval (RSI) was either 100 or 1,000 ms, manipulated between blocks. Task alternations were slower than task repetitions, and this switch cost was greater at the short RSI than at the long RSI (310 and 94 ms, respectively). Additionally, subjects produced more task repetitions than expected if the tasks were performed in a random sequence. These results show costs associated with a voluntary task switch, when subjects must actively control the choice of the task to be performed.